From leave it to beaver to modern family: The influence of family structure on adoption attitudes. Issue 4 (1st October 2020) - Curme, Patrick; Schwieters, Katelyn; Kleyman, Kerry S.
Abstract: How do social and religious views influence attitudes of the capability and appropriateness of a prospective adoptive parent? The present experiment presents an investigation into the sources of attitudes and biases towards gay and lesbian couples and single parents in an adoption scenario. The author discusses existing theories of discrimination against LGBT populations and outgroups in general, including Social Dominance Orientation and Religious Fundamentalism, all highly predictive of LGBT bias. Current forms of adoption discrimination against nontraditional adopters from public policy makers and adoption agencies alike is explored and an empirical test of these discriminatory trends was created. Proposed adoption scenarios were presented and participant sentiments about the appropriateness of the adoption and prospective parent(s) were assessed. The direct and interactive effects of overt social and religious views were measured and these factors were clearly demonstrated to influence adoption attitudes. The present research aimed to uncover modern sources of prejudice towards gay and lesbian and single adoptive parents and offer new avenues of exploration into the foundation of such discrimination.